Ephram Chun is teaching functions to his class. He tells that he has a function which is in the form:
f ( x ) = a x 2 a + 1 + b x 2 b + 1 + c x 2 c + 1 + d x 2 d + 1 + 6 1
If f ( 1 3 ) = − 1 3 , what is the value of f ( − 1 3 ) ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We can write out f ( 1 3 ) as − 1 3 = a ( 1 3 ) 2 a + 1 + b ( 1 3 ) 2 b + 1 + c ( 1 3 ) 2 c + 1 + d ( 1 3 ) 2 d + 1 + 6 1 which is equal to − 7 4 = a ( 1 3 ) 2 a + 1 + b ( 1 3 ) 2 b + 1 + c ( 1 3 ) 2 c + 1 + d ( 1 3 ) 2 d + 1 . Let's write the form out for f ( − 1 3 ) . f ( − 1 3 ) = a ( − 1 3 ) 2 a + 1 + b ( − 1 3 ) 2 b + 1 + c ( − 1 3 ) 2 c + 1 + d ( − 1 3 ) 2 d + 1 + 6 1 we can subtract 6 1 from both sides to get f ( − 1 3 ) − 6 1 = a ( − 1 3 ) 2 a + 1 + b ( − 1 3 ) 2 b + 1 + c ( − 1 3 ) 2 c + 1 + d ( − 1 3 ) 2 d + 1 We see that a ( − 1 3 ) 2 a + 1 + b ( − 1 3 ) 2 b + 1 + c ( − 1 3 ) 2 c + 1 + d ( − 1 3 ) 2 d + 1 is the opposite of a ( 1 3 ) 2 a + 1 + b ( 1 3 ) 2 b + 1 + c ( 1 3 ) 2 c + 1 + d ( 1 3 ) 2 d + 1 Therefore the answer is f ( − 1 3 ) = − 7 4 ∗ − 1 + 6 1 = 1 3 5
Problem Loading...
Note Loading...
Set Loading...
Similar solution as @Ephram Chun 's
Let g ( x ) = a x 2 a + 1 + b x 2 b + 1 + c x 2 c + 1 + d x 2 d + 1 . Note that g ( x ) is an odd function . That is g ( − x ) = − g ( x ) . Then we have:
f ( x ) f ( 1 3 ) ⟹ g ( 1 3 ) f ( − 1 3 ) = g ( x ) + 6 1 = g ( 1 3 ) + 6 1 = − 1 3 = f ( 1 3 ) − 6 1 = − 1 3 − 6 1 = − 7 4 = g ( − 1 3 ) + 6 1 = − g ( 1 3 ) + 6 1 = − ( − 7 4 ) + 6 1 = 1 3 5 Since g ( x ) is odd,